Osady ściekowe na plantacji wierzby energetycznej = Sewage sludges on the willow plantation - Sieciechowicz, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents literature data analysis concerning amount of sewage sludge produced in Poland and the way of sewage sludge final management. Utilisation of sewage sludge as an energy willow fertiliser was noticed in methods given in the paper.
Keywords: osady ściekowe; wierzba energetyczna; sewage sludge; energy willow